Evaluation of the effect of shift working and sleep quality on semen parameters in men attending infertility clinic. (12th May 2021) - Demirkol, Mehmet Kutlu; Yıldırım, Abdullah; Gıca, Şakir; Doğan, Neslihan Temiz; Resim, Sefa
Abstract: We aimed to evaluate the effect of shift work on semen parameters together with the effect of sleep quality in men attending infertility clinic. The participants were divided into two groups as follows: 104 shift worker men (Group 1) and 116 nonshift worker men (Group 2). Groups were compared in terms of semen parameters, Depression Anxiety Stress Scale‐21 (DASS‐21), and Pittsburg Sleep Quality Index (PSQI) scores. A higher rate of oligozoospermia and poor sleep quality and a lower mean normal morphology percentage was observed in shift workers than nonshift workers ( p  = .006, .039 and .036 respectively). In addition, a positive correlation was seen between sleep duration and sperm concentration, while a negative correlation was found between sleep latency and total sperm count. Shift working together with high PSQI score was also a significant association with oligozoospermia when controlling for the other variables of age, total testosterone, DASS‐21 stress score, smoking and varicocele (OR = 2.11, 95% CI 1.03–4.34 and OR = 1.18, 95% CI 1.01–1.39 respectively). In this study, infertile shift workers had a lower percentage of normal morphology and higher rates of oligozoospermia and poor sleep quality. Considering that shift workers have lower sleep quality, it seems that shift working negatively affects the circadian rhythm.